Transformasi Digital dan Sistem Informasi Manajemen: Tinjauan Literatur tentang Peran Teknologi Digital dalam Meningkatkan Efektivitas Organisasi - Cut Karina Putri; Mili Yana Hamisa; Ratna Dewita (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
Digital transformation has fundamentally changed the way organizations manage information, formulate strategies, and create value. Amidst these changes, Management Information Systems (MIS) no longer function merely as administrative support tools but have evolved into a strategic foundation that determines the overall competitiveness of organizations. This article aims to synthesize the latest literature on the role of digital technology in improving organizational effectiveness through a Management Information Systems perspective. This study applies the Systematic Literature Review (SLR) method with PRISMA guidelines to collect and analyze various studies relevant to digital transformation and management information systems. The literature used is sourced from the latest scientific publications from the period 2022–2026 so as to reflect the latest research developments in the field. The results of the synthesis identify four key variables as determinants of organizational effectiveness in the digital era: digital transformation, the quality of Management Information Systems, the quality of information, and decision-making capabilities. Digital transformation has been proven to have a positive contribution to organizational effectiveness, but its influence does not occur automatically, but is conditioned by the quality of the MIS, the quality of the information produced, and managerial capabilities in utilizing that information. The study results indicate that research on digital transformation and management information systems still has several limitations, particularly regarding the integration of research variables, understanding the implementation process, and examining the Indonesian context. Therefore, further research is expected to develop more comprehensive models and approaches to enrich our understanding of the impact of digital transformation on organizational performance.